DEVELOPING BLUEPRINTS FOR THE IMPLEMENTATION OF VIRTUAL REALITY ROLE-PLAY TO IMPROVE COMMUNICATION AND DIGITAL SKILLS IN TRANSNATIONAL COLLABORATIVE LEARNING (Proceedings of the International Conference on Education, 2022)
Virtual collaborative learning and teaching benefits from using immersive technologies to develop both key competences, such as collaboration, virtual communication, and problem-solving skills, and social and digital skills. VR, which is understood as a scientific and technical field that uses information technology and behavioural interfaces to simulate the individual behaviour of 3D entities in the virtual world is justified by concepts such as immersion and interactivity (technical dimension) and the construction of presence (psychological dimension). As such, the Hotel Academy project aimed at the development of a joint curriculum that allows for virtual interdisciplinary, international, and intercultural collaboration and virtual exchange (COIL) between three European universities from Cyprus, France, and Germany in the field of hospitality management. Based on a thematic analysis of focus group discussions, semi-structured interviews with different stakeholders (2+4 sessions, N=13) and participatory observations in VR role-plays, this paper presents findings from a summative validation of the underlying didactical framework. This includes the dimensions of didactics, organization, technology, economy, education system, institution, and individuals. Based on the validation of the underlying framework, transnational, and cross-institutional blueprints (e.g., multiplier strategy, prototyping strategy, synergetic strategy) are developed for the implementation of this specific VR environment in higher education institutions. Such blueprints are no simple representation of the universities involved in this project but emerged from our qualitative data analysis as part of the recommendations from the involved stakeholders and experts. The blueprints demonstrate empirically grounded archetypes of different states in which higher education institutions can locate themselves. Finally, conclusions are drawn regarding practical implications of the implementation of virtual role-plays and regarding future research directions.
Keywords: transnational/cross-institutional cooperation; virtual collaborative learning; virtual reality